Association of hyperglycaemia at admission with in-hospital mortality and severity of illness among patients with COVID-19. - Zaman, Sadaf; Khan, Mujeeb; Khatana, Arif; Rehman, Fazal Ur; Umar, Muhammad; Meraj, Lubna (Journal of Rawalpindi Medical College, 2022)
Objectives The association between hyperglycemia at admission and COVID-19 severity and in-hospital mortality is an area of active medical research. Our study aims to explore this association across diabetics and hyperglycemic patients while keeping normoglycemic patients as control. Methods This retrospective cohort study involved a total of 90 patients with confirmed diagnosis of COVID-19 infection. Patients were divided into three equal groups based on their history and BSR levels (diabetics, hyperglycemic, normoglycemic). Various laboratory parameters and inflammatory markers were compared across the study groups using Kruskal Wallis test. Finally, chi-square test was use to assess the association of severity and mortality across the study groups. Results Out of 90 patients, 38 (42.2%) were males with a mean age of 57.1 ± 14.7 years. Serum ferritin, LDH and lymphocyte levels were significantly higher in diabetics and hyperglycemic patients than in normal COVID-19 patients (p<0.05). hyperglycemia at admission was significantly associated with disease severity (p=0.03) but not with in-hospital morality (p=0.07). Conclusion Patients with diabetes and stress hyperglycemia have increased levels of inflammatory markers than normoglycemic patients. Hyperglycemia at admission is associated with poor COVID-19 severity. More studies a required to validate and further explore this relationship.